Memahami Ragam Qiraat dalam Surah Al- Ma'idah dan Implikasi Maknanya - Siti Nur Ismah; Nur Laili Nabilah Nazahah Najiyah; Fathinatuzzayyan Al Kamilah (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
This study aims to explore the various qiraat found in Surah Al-Ma’idah and their interpretative implications in Tafsir 10 Qiraat dan Tadabbur Surah Al-Ma’idah by Saiful Islam Mubarak. Employing a qualitative library research method, the primary source is Mubarak’s tafsir, supplemented by relevant secondary literature. Data analysis involves condensation, presentation, and conclusion drawing. The findings reveal 24 verses in Surah Al-Ma’idah containing qiraat variations. Mubarak elaborates on each variant, the reciters (imam and rawi), and the semantic implications. Of these, seven verses exhibit vowel variations without altering meaning or script; another seven show vowel and semantic changes while retaining the script; six involve consonantal and semantic changes with identical rasm; and the remaining three differ in letters, script, and meaning. These results underscore the value of qiraat-based exegesis as a method that enhances interpretive depth and supports the contextual development of Qur’anic commentary by Nusantara scholars.